Phosphomimetic Dicer S1016E triggers a switch to glutamine metabolism in gemcitabine-resistant pancreatic cancer - Ji Min Park; Jei-Ming Peng; Yu-Shiuan Shen; Chia-Ying Lin; Tung-Wei Hsu; Yen-Hao Su; Hsin-An Chen; Charupong Saengboonmee; Jung-Su Chang; Ching-Feng Chiu; Yan-Shen Shan (Elsevier, 2022)
Objective: Dicer is an enzyme that processes microRNAs (miRNAs) precursors into mature miRNAs, which have been implicated in various aspects of cancer progressions, such as clinical aggressiveness, prognosis, and survival outcomes. We previously showed that high expression of Dicer is associated with gemcitabine (GEM) resistance in pancreatic ductal adenocarcinoma (PDAC); thus, in this study, we aimed to focus on how Dicer is involved in GEM resistance in PDAC, including cancer prognosis, cell proliferation, and metabolic regulation. Methods: We generated stable shRNA knockdown of Dicer in GEM-resistant PANC-1 (PANC-1 GR) cells and explored cell viability by MTT and clonogenicity assays. Metabolomic profiling was employed to investigate metabolic changes between parental cells, PANC-1, and PANC-1 GR cells, and further implied to compare their sensitivity to the glutaminase inhibitor, CB839, and GEM treatments. To identify putative phosphorylation site involves with Dicer and its effects on GEM resistance in PDAC cells, we further generated phosphomimetic or phosphomutant Dicer at S1016 site and examined the changes in drug sensitivity, metabolic alteration, and miRNA regulation. Results: We observed that high Dicer levels in pancreatic ductal adenocarcinoma cells were positively correlated with advanced pancreatic cancer and acquired resistance to GEM. Metabolomic analysis indicated that PANC-1 GR cells rapidly utilised glutamine as their major fuel and increased levels of glutaminase (GLS): glutamine synthetase (GLUL) ratio which is related to high Dicer expression. In addition, we found that phosphomimetic Dicer S1016E but not phosphomutant Dicer S1016A facilitated miRNA maturation, causing an imbalance in GLS and GLUL and resulting in an increased response to GLS inhibitors. Conclusion: Our results suggest that phosphorylation of Dicer on site S1016 affects miRNA biogenesis and glutamine metabolism in GEM-resistant pancreatic cancer.